2014
DOI: 10.1007/s40333-014-0044-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and historical demography of Malus sieversii in the Yili Valley and the western mountains of the Junggar Basin, Xinjiang, China

Abstract: Malus sieversii, a wild progenitor of domesticated apple, is distributed in western Xinjiang of China, eastern part of Kazakhstan and Kyrgyzstan in Central Asia. To well understand the genetic structure and the historical demography of this important germplasm resource, we sampled 15 populations with 110 individuals of Malus sieversii from the Yili Valley and the western mountains of the Junggar Basin, Xinjiang, and sequenced two nrDNA fragments for these 110 individuals. Meanwhile, we modeled and compared spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
(35 reference statements)
1
16
1
1
Order By: Relevance
“…2). However, using sequences from the gene LEAFY, we found that population GL did not have the highest genetic diversity (Zhang et al 2015). Still, levels of genetic diversity among the six populations was ordered differently between our study and previous studies.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…2). However, using sequences from the gene LEAFY, we found that population GL did not have the highest genetic diversity (Zhang et al 2015). Still, levels of genetic diversity among the six populations was ordered differently between our study and previous studies.…”
Section: Discussioncontrasting
confidence: 82%
“…These selected microsatellite primers were tagged with a fluorescent dye at the 5¢ end. The PCR amplification program followed the protocols of Zhang et al (2015), except for the SSR primers used. PCR products were checked with 8% non-denaturing polyacrylamide gel electrophoresis, separated and visualized using an ABI 3730 automated sequencer by Sangon Biotech (Shanghai), and read with the software GeneMapper.…”
Section: Nssr Molecular Laboratory Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the important role of M. sieversii in apple breeding, this species has been studied in terms of its genetic diversity and population structure Richards et al, 2009), gene flow with Malus domestica (Cornille et al, 2013b), historical demography (Zhang et al, 2015) and molecular basis for abiotic resistance (Forsline et al, 2003). As to the S-alleles controlling cross-compatibility, few studies have investigated them in M. sieversii, however, such alleles have been extensively studied for apple cultivars and other fruit crops within Rosaceae (Broothaerts, 2003;Sanzol, 2009;Long et al, 2010) owing to the importance of SI to fruit production.…”
Section: Introductionmentioning
confidence: 99%
“…Although wild apple forests occupy an estimated 93% among the wild fruit forests in Chinese Tianshan, compared with 78% for the central Asian portion (Lin & Lin, 2000), the wild apple forests are not well studied. The wild apple M. sieversii is the primary progenitor of all cultivated domesticated apple species (Duan et al, 2017;Harris, Robinson, & Juniper, 2002;Hokanson et al, 1998;Richards et al, 2009;Zhang, Zhang, & Wang, 2015) and therefore is a globally important resource for apple breeding because of the rich genetic diversity. Thus, the ex and in situ preservation of this species is globally important (Hokanson et al, 1998;Yang et al, 2016).…”
mentioning
confidence: 99%